2017
DOI: 10.1093/gigascience/giw015
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the total number of phosphoproteins and phosphorylation sites in eukaryotic proteomes

Abstract: BackgroundPhosphorylation is the most frequent post-translational modification made to proteins and may regulate protein activity as either a molecular digital switch or a rheostat. Despite the cornucopia of high-throughput (HTP) phosphoproteomic data in the last decade, it remains unclear how many proteins are phosphorylated and how many phosphorylation sites (p-sites) can exist in total within a eukaryotic proteome. We present the first reliable estimates of the total number of phosphoproteins and p-sites fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
103
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(108 citation statements)
references
References 54 publications
0
103
0
Order By: Relevance
“…Protein kinases and phosphatases oppositely regulate the most common post-translational modification, phosphorylation. A recent phosphoproteomics study estimated that nearly half of the total proteins from any of human, mouse or yeast are phosphoproteins (Vlastaridis et al, 2017). Therefore, it is reasonable to estimate that a comparable ratio of apicomplexan proteins is under the regulation of phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Protein kinases and phosphatases oppositely regulate the most common post-translational modification, phosphorylation. A recent phosphoproteomics study estimated that nearly half of the total proteins from any of human, mouse or yeast are phosphoproteins (Vlastaridis et al, 2017). Therefore, it is reasonable to estimate that a comparable ratio of apicomplexan proteins is under the regulation of phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have clarified specific differences between NOX‐dependent and NOX‐independent NETosis, the underlying mechanisms of NETosis have not been fully elucidated. Phosphorylation is the most frequent post‐translational modification of proteins . In this study, Phosphoproteomics was employed to gain insight into the molecular mechanisms underlying NETosis and discover the common factors associated with both NOX‐dependent and NOX‐independent NETosis.…”
mentioning
confidence: 99%
“…Currently, sophisticated analytical methods (e.g., mass spectrometry, functional interaction traps, affinity chromatography) have taken great strides recently: they have facilitated the determination of the high‐throughput phospho‐proteome within many species and tissues, although the exact phospho landscape is impossible to determine, because of rapid turnover and the inevitable loss of material during the analytical extraction process. [ 2,24,25 ] It was found that 86% of all phosphorylated residues are serine, followed by 12% threonine and only 1.8% tyrosine. [ 5,24,25 ] These powerful technologies allowed the creation of public databases that report the exact and comprehensive phospho sites found in vivo for multiple species models.…”
Section: Introductionmentioning
confidence: 99%